Brainstem Correlates of Pathological Laughter and Crying Frequency in ALS - Tu, Sicong; Huang, Mengjie; Caga, Jashelle; Mahoney, Colin J.; Kiernan, Matthew C. (Frontiers in Neurology, 2021)
Pseudobulbar affect is a disorder of emotional expression commonly observed in amyotrophic lateral sclerosis (ALS), presenting as episodes of involuntary laughter, or crying. The objective of the current study was to determine the association between frequency of pathological laughter and crying (PLC) episodes with clinical features, cognitive impairment, and brainstem pathology. Thirty-five sporadic ALS patients underwent neuropsychological assessment, with a subset also undergoing brain imaging. The Center for Neurological Study Lability Scale (CNS-LS) was used to screen for presence and severity of pseudobulbar affect (CNS-LS ≥ 13) and frequency of PLC episodes. Presence of pseudobulbar affect was significantly higher in bulbar onset ALS (p = 0.02). Frequency of PLC episodes was differentially associated with cognitive performance and brainstem integrity. Notably pathological laughter frequency, but not crying, showed a significant positive association with executive dysfunction on the Trail Making Test B-A (R2 = 0.14, p = 0.04). Similarly, only pathological laughter frequency demonstrated a significant negative correlation with gray matter volume of the brainstem (R2 = 0.46, p < 0.01), and mean fractional anisotropy of the superior cerebellar peduncles (left: R2 = 0.44, p < 0.01; right: R2 = 0.44, p < 0.01). Hierarchical regression indicated brainstem imaging in combination with site of symptom onset explained 73% of the variance in pathological laughter frequency in ALS. The current findings suggest emotional lability is underpinned by degeneration across distinct neural circuits, with brainstem integrity critical in the emergence of pathological laughter.